INVESTIGATION OF ANTICANCER EFFECT OF ACETIC ACID DERIVATIVES CONTAINING 1,2,4-TRIAZOLE MOIETY AGAINST TWO DIFFERENT CANCER CELL LINES - Parlak, Akif Evren (Parlar Scientific Publications (P S P), 2018)
The purpose of this study is to investigate the anticancer activity of [(4-substituted-5-pyridin-4yl-4H-1,2,4-triazol-3-yl)thio] acetic acid derivatives and to determine their pharmacological potential. In this study, the effects of test compounds on human breast cancer (MCF-7) and murine leukemia cells (L1210) were investigated in vitro. In this in vitro study, it was determined that test compounds inhibited the proliferation of cancerous cells in different cancer cell lines significantly higher compared to the control group. Test compounds were found to reduce the ratio of live cancer cells in the control group, depending on the dose and time interval in the administration group. As a result, it can be stated that test compounds have anticancer activity in different cancer series in in vitro conditions.
Keywords: Triazole; anticancer; breast cancer; leukemia